2015
DOI: 10.1016/j.dam.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Decycling bubble sort graphs

Abstract: a b s t r a c tThe decycling number of a graph G is the minimum number of vertices whose removal from G results in an acyclic subgraph. In this paper we show that the decycling number f (n) of the bubble sort graph B n satisfies these inequalities:.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…(2n − 3)/4(n − 1), respectively, where an n-bubble sort graph has n! nodes [12]. Xu et al have shown that the lower and upper bounds of the number of nodes of an MFNS in a crossed cube are 2 n−1 (n − 2)/(n − 1) and 2 n−1 , respectively [13].…”
Section: Related Workmentioning
confidence: 99%
“…(2n − 3)/4(n − 1), respectively, where an n-bubble sort graph has n! nodes [12]. Xu et al have shown that the lower and upper bounds of the number of nodes of an MFNS in a crossed cube are 2 n−1 (n − 2)/(n − 1) and 2 n−1 , respectively [13].…”
Section: Related Workmentioning
confidence: 99%
“…Focardi et al gave bounds for the decycling number of hypercubes [10]. Many results on the upper bound of the decycling number are proposed, like star graphs [21], (n, k)star graphs [23], bubble sort graphs [24], and so forth [6,11,16,18,19,22,27].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the bound on the decycling number of hypercubes was continued in [2] and [13]. This body of work inspired research on the decycling number of other practical network structures [20,21]. In more traditional graph theoretic directions, there has been progress on bounding the decycling of regular graph in general [14], as well as for cubic graphs specifically [15,16] including finding the exact decycling number of the (generalized) Petersen graph [8].…”
Section: Introductionmentioning
confidence: 99%